SISTEM MODULAR PADA PERANCANGAN LEMARI BAJU DENGAN KONSEP SUSTAINABLE DESIGN - Terbit Setya Pambudi; Gabriella Chrismaditya Putri Mawarni; Dandi Yunidar (Gorga : Jurnal Seni Rupa, 2024)
The progress of the local and global furniture industry opens up opportunities for Indonesia to return to producing local furniture to support the economy. Millennials as the largest furniture market share in Indonesia have an interest in modular furniture. Modular furniture systems provide ease of mobilization, installation and customization which helps optimize the use of increasingly limited residential land. Apart from that, the need for furniture that is able to adapt according to user needs is also a simple application of the sustainable design concept. The concept of sustainable design refers to intelligent human thought patterns and actions that are in harmony with and respect nature. In the context of research, this concept is realized in the form of a furniture modulation system that can adapt to user needs. This research focuses on designing modular wardrobes that accommodate millennial needs. The design was carried out using design methods: observation, interviews, questionnaires, and literature study, followed by a design process using the User-Centered Design method and identification of user personas. The furniture designed is furniture with a combination of on-a-frame & single bodied modular systems with a knockdown system for easy mobilization and customizationKeywords: EcoLifestyle, bags, modular, sustainable designAbstrakKemajuan industri furnitur lokal dan global membuka peluang bagi Indonesia untuk kembali memproduksi furnitur lokal demi mendukung perekonomian. Milenial sebagai pangsa pasar furnitur terbesar di Indonesia memiliki ketertarikan terhadap furnitur modular. Sistem furnitur modular menyediakan kemudahan mobilisasi, instalasi, dan kustomisasi yang membantu optimalisasi penggunaan lahan huni yang semakin terbatas. Selain itu kebutuhan furniture yang mampu berdaptasi sesuai kebutuhan pengguna juga merupakan penerpan sederhana dari konsep sustainable design. Konsep sustainable design mengacu pada pola pikir dan tindakan manusia secara cerdas yang selaras dan menghargai alam. Dalam konteks penelitian konsep tersebut diwujudkan dalam bentuk system modulasi furniture yang bisa beradaptasi dengan kebutuhan pengguna. Penelitian ini berfokus untuk merancang lemari modular yang mengakomodasi kebutuhan milenial. Perancangan dilakukan dengan metode desain: observasi, wawancara, kuesioner, dan studi literatur, dilanjutkan dengan proses perancangan menggunakan metode User-Centered Design dan identifikasi persona pengguna. Furnitur yang dirancang adalah furnitur dengan gabungan sistem modular on-a-frame & single bodied dengan sistem knockdown untuk memudahkan mobilisasi dan kustomisasiKata Kunci: Modular, Furniture, Lemari, Sustainable DesignAuthors:Terbit Setya Pambudi : Universitas TelkomGabriella Chrismaditya Putri Mawarni : Universitas TelkomDandi Yunidar : Universitas TelkomReferencesBadan Pusat Satistik (BPS). (2021). Hasil Sensus Penduduk 2020. Diambil Kembali dari https://demakkab.bps.go.id/news/2021/01/21/67/hasil-sensus-penduduk-2020.htmlBesson, A. (2019). A Call for more Modular Durability in Design. Diambil Kembali dari https://asiapacificcircle.org/asia-pacific-insights-trends/more-modular-durability-in-design-alexandre-besson/Durif, F., Boivin, C., & Julien, C. (t.thn.). In Search of a Green Product Definition. Innovative Marketing, 6, 25-33.Garip, B., Saglar, N., Politecnico, O., Torino, D., Garip, S., & GÃ¼zelci, O. (2019). Flexible and Modular Furniture Design for Changing Living Environments. The XXIXTH International.Halim, W., Kusbiantoro, K., Lesmana, C., Gunawan, IV. (2023). Perancangan Bangunan Modular Penunjang Green Economy Untuk Hunian Resiliensi Bencana. Medan. Gorga: Jurnal Seni Rupa. 12 (01), 124 “ 131.Hara, T., Sakao, T., & Fukushima, R. (2019). Customization of product, service, and product/service system: what and how to design. doi:10.1299/mer.18-00184.Kementrian Perindustrian Republik Indonesia. (2021). Tumbuh 8 Persen, Industri Furnitur Tangguh Hadapi Dampak Pandemi. Diambil kembali dari https://www.kemenperin.go.id/artikel/22793/Tumbuh-8-Persen,-Industri- Furnitur-Tangguh-Hadapi-Dampak-PandemiMcLennan, J. F. (2004). The Philosophy of Sustainable Design: The Future of Architecture. United Kingdom. Ecotone.Muttaqien, TZ. & Adilihung, H. (2023). Pemanfaatan Sisa Bahan Produksi Menjadi Material Siap Pakai Dan Penerapanya Pada Produk Dekorasi Rumah. Medan. Gorga: Jurnal Seni Rupa, 12(01), 224-229Pambudi, TS., Arliando, P., Muttaqien, TZ. (2022). Perancangan Tas Modular Sebagai Produk Eco Lifestyle. Medan. Gorga: Jurnal Seni Rupa, 11(02), 499-564Soewardikoen, D. (2019). Metodologi Penelitian: Desain Komunikasi Visual. Yogyakarta: PT Kanisius.Smardzewski, J. (2015). Furniture Design. Switzerland. Springer International Publishing doi:10.1007/978-3-319-19533-9Tseng, M., Wang, Y., & Jiao, R. (2018). Modular Design. The International Academy for Production (eds) CIRP Encyclopedia of Production Engineering. doi:10.1007/978-3-642-35950-7_6460-4UNEP 2009 Annual Report. Seizing The Green Opportunity. Nairobi: UNEP Publishing Service SectionUzoegbo, H. (2016). 8 - Dry-stack and compressed stabilised earth-block construction. Harries, K. and Sharma, B., Eds., Nonconventional and Vernacular Construction Materials, 205-249. doi:10.1016/B978-0-08-100038-0.00008-1Wijaya, D., & Anastasia, N. (2021). Pertimbangan Generasi Milenial pada Kepemilikan Rumah dan Kendala Finansial. Diambil kembali dari https://jmap.mappi.or.id/index.php/journal penilai/article/view/23/10Xue, D., Hua, G., Mehrad, V., & Gu, P. (2012). Optimal Adaptable Design for Creating the Changeable Product Based on Changeable Requirements Considering the Whole Product Life-Cycle. Journal of Manufacturing Systems, 31(1), 59-68. doi:10.1016/j.jmsy.2011.04.003